The effects of sample handling and N‐phenylmaleimide on concentration of adrenocorticotrophic hormone in equine plasma. (7th October 2014) - Rendle, D. I.; Litchfield, E.; Gough, S.; Cowling, A.; Hughes, K. J.
Summary Reasons for performing study Previous reports suggest that adrenocorticotrophic hormone (ACTH) degrades rapidly, limiting its use as a diagnostic test. Objectives This study quantified effects of processing delays on ACTH concentrations and investigated the addition of N‐phenylmaleimide (maleimide), a protease inhibitor, as a means of reducing ACTH degradation. Study design Experimental study. Methods Venous blood was collected from 8 healthy horses and 8 horses with pituitary pars intermedia dysfunction (PPID) with a range of ACTH concentrations. Baseline ACTH concentrations were established immediately using a chemiluminescent assay. Plasma samples were then: 1) centrifuged immediately, 2) centrifuged immediately with the addition of maleimide, or 3) allowed to separate by gravity followed by the addition of maleimide, before all samples were stored at 22°C and analysed at 4, 8, 24 and 48 h post collection. A linear mixed effects model and Bland‐Altman analyses were performed. Significance was set at P < 0.05. Results No significant effect of plasma treatment (P = 0.1) on change in ACTH concentration was identified. However, significant effects of horse health status (P<0.001) and time (P<0.001) on change in ACTH concentration were identified. No significant interactions were found. Significant decreases in ACTH concentration occurred in horses with PPID between 4 and 8 h after blood collection. In non‐PPID horses, the decrease in ACTH concentration over time was not significant. Agreement with baseline values decreased over time and was greater for non‐PPID horses than for PPID horses. Conclusions Clinically useful results are still obtained if ACTH concentration is measured up to 48 h after sample collection. Allowing samples to separate by gravity rather than centrifugation did not have a significant effect on ACTH concentration, and the addition of maleimide was of no benefit.